COMMUNICATION DA'WAH IN THE ART OF NASYEED MUSIC (A Study of Music Art at Sunan Drajat Islamic Boarding School) - SITI ROHMAH; ABDUL MUHID (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2020)
This article discusses preaching communication through senior nasyid / qasidah music at Sunan Drajat Lamongan Islamic Boarding School. Religion and culture in Indonesia, when viewed from the context of Islam that is developing and living in the archipelago has become a symbiotic relationship. In order for people to understand religion, methods are needed that can be used by religion that can be easily resolved by the community. Da'wah that is done in a contemporary style will be more easily accepted, one of them with music that contains lyrics of advice or propaganda. Music is used as a means of delivering da'wah in the pantura area (north coast) specifically and Indonesian society in general because Prof. Dr. KH. Abdul Ghofur takes care of the Sunan Drajat Islamic Boarding School there needs to be new innovations in preaching in this modern era, as well as launching Mbah Kanjeng Sunan Drajat's footsteps using senior music as a means of spreading Islam in the north last year. Islam throughout the developing world cannot be separated from the culture of society.Keywords: Da'wah communication, Nasyid Music, Sunan Drajat Islamic Boarding School.